Top Posts in Big Companies Firmly in Male Hands - Elke Holst; Anne-Katrin Stahn (Weekly Report, 2007)
Women hold only 7.8% of the supervisory board posts in the 200 biggest companies (Top 200) in Germany - outside finance -, and three of four (76.0%) are workers representation delegates. More than one third of these companies do not have a woman on the supervisory board at all. The share of women on management boards is even smaller. In the 100 biggest companies (Top 100) there is only one woman on a management board. There are only eleven in the Top 200, a share of a good one percent. These figures show that the aim of equality of opportunity for men and women in top influential posts in large firms is still a long way off. Among European countries Norway is in the lead with women accounting for just under one third of the seats on the decision-making bodies of the 50 biggest companies traded on the stock exchange. The other Scandinavian countries are also above the average, as are the East European EU member states. Germany is in the middle with 11%. According to information from the European Commission Germany is at the lower end of the scale of countries in the share of women in more broadly defined management posts, with around one quarter. Even countries with a relatively low percentage of women in employment, like Spain and Italy, have clearly higher shares of women on this level of the hierarchy than Germany, with just under one third each.
Keywords: 330; Women; Supervisory boards; Management Positions